7h2-56h=-112
7h2-56h+112=0 7(h2-8h+16)=0
7(h-4)2=0
(h-4)2=0
h-4=0
h=4
7(16)-56(4)=-112
112-224=-112 so the answer is correct.
If: 7h+4 = -80 then h = -12
4h + 7h - 16 = 6 Combine like terms: 11h - 16 = 6 Add 16 to both sides: 11h = 22 Divide both sides by 11: h = 2
h = 0.538462 14 + 5h + 2h = 5h + 28h 14 + 7h = 33h 14 + 7h - 7h = 33h - 7h 14 = 26h 14/26 = 26/26h 0..538462 = h
The value of h is 9
7h - 2 - 51 is an expression NOT an equation. An expression cannot be solved for the value of a variable.
h = -5 -7 * -5 = 35 A negative times a negative equals a positive.
-7h = 35h = -5
7h+39=60 Take away 39 from both sides (called isolating your variable) 7h=21 Divide by seven, because (I assume) you are looking for h, not 7h h=3 And to check: 7(3)+39=60 21+39=60 60=60
I would not fully go by my answer but I think its h=6
(7h + 35) / (-7) = (7h)/(-7) + (35)/(-7) = (-h) + (-5) = - (h + 5)
Unless you have a value for 'h', the answer will just be an expression: 10 + 7h
In the expression 7h + 3, the coefficient is 7, which is the numerical factor of the variable h. The constant is 3, which is a term without a variable attached to it. Coefficients and constants are essential components in algebraic expressions and equations, helping determine the value of the expression based on the variables involved.